Teks Satua Betara Watugunung Dalam Cerita Rakyat Daerah Bali: Analisis Struktur dan Fungsi - Dias Febriadiana, Ni Made (Humanis; Vol 22 No 2 (2018)DO - 10.24843/JH.2018.v22.i02.p10, 2018)
The title of this paper is “Text Betara Watugunung Story in Balinese Area Story; Analyze of structure and function”. This paper is using structural theory, and function theory. The aims of this paper is to describe narrative structure in text Betara Watugunung Story in Balinese Area Story and analysis the function. The step of provision the data are using method of interview and method of reading with recording technique and translation technique. We analysis the data by qualitative methods in this stage is also supported by analytical descriptical technique. At presentation stage of data result of method used is informal method assisted with inductive and deductive technique.